Nanotopography Drives Stem Cell Fate Toward Osteoblast Differentiation Through α1β1 Integrin Signaling Pathway. Issue 3 (March 2014) - Rosa, A.L.; Kato, R.B.; Castro Raucci, L.M.S.; Teixeira, L.N.; de Oliveira, F.S.; Bellesini, L.S.; de Oliveira, P.T.; Hassan, M.Q.; Beloti, M.M.
ABSTRACT The aim of our study was to investigate the osteoinductive potential of a titanium (Ti) surface with nanotopography, using mesenchymal stem cells (MSCs) and the mechanism involved in this phenomenon. Polished Ti discs were chemically treated with H2SO4/H2O2 to yield nanotopography and rat MSCs were cultured under osteogenic and non‐osteogenic conditions on both nanotopography and untreated polished (control) Ti surfaces. The nanotopography increased cell proliferation and alkaline phosphatase (Alp) activity and upregulated the gene expression of key bone markers of cells grown under both osteogenic and non‐osteogenic conditions. Additionally, the gene expression of α1 and β1 integrins was higher in cells grown on Ti with nanotopography under non‐osteogeneic condition compared with control Ti surface. The higher gene expression of bone markers and Alp activity induced by Ti with nanotopography was reduced by obtustatin, an α1β1 integrin inhibitor. These results indicate that α1β1 integrin signaling pathway determines the osteoinductive effect of nanotopography on MSCs. This finding highlights a novel mechanism involved in nanosurface‐mediated MSCs fate and may contribute to the development of new surface modifications aiming to accelerate and/or enhance the process of osseointegration. J. Cell. Biochem. 115: 540–548, 2014. © 2013 Wiley Periodicals, Inc.